Nutrient acquisition, soil phosphorus partitioning and competition among trees in a lowland tropical rain forest. Issue 4 (6th March 2017) - Nasto, Megan K.; Osborne, Brooke B.; Lekberg, Ylva; Asner, Gregory P.; Balzotti, Christopher S.; Porder, Stephen; Taylor, Philip G.; Townsend, Alan R.; Cleveland, Cory C.
Summary: We hypothesized that dinitrogen (N2 )‐ and non‐N2 ‐fixing tropical trees would have distinct phosphorus (P) acquisition strategies allowing them to exploit different P sources, reducing competition. We measured root phosphatase activity and arbuscular mycorrhizal (AM) colonization among two N2 ‐ and two non‐N2 ‐fixing seedlings, and grew them alone and in competition with different inorganic and organic P forms to assess potential P partitioning. We found an inverse relationship between root phosphatase activity and AM colonization in field‐collected seedlings, indicative of a trade‐off in P acquisition strategies. This correlated with the predominantly exploited P sources in the seedling experiment: the N2 fixer with high N2 fixation and root phosphatase activity grew best on organic P, whereas the poor N2 fixer and the two non‐N2 fixers with high AM colonization grew best on inorganic P. When grown in competition, however, AM colonization, root phosphatase activity and N2 fixation increased in the N2 fixers, allowing them to outcompete the non‐N2 fixers regardless of P source. Our results indicate that some tropical trees have the capacity to partition soil P, but this does not eliminate interspecific competition. Rather, enhanced P and N acquisition strategies may increase the competitive ability of N2 fixers relative to non‐N2 fixers.